Predicting anisotropic thermal displacements for hydrogens from solid-state NMR: a study on hydrogen bonding in polymorphs of palmitic acid. Issue 13 (12th February 2018) - Wang, Luther; Uribe-Romo, Fernando J.; Mueller, Leonard J.; Harper, James K.
Abstract : Solid-state NMR and DFT methods establish anisotropic thermal displacements for COOH hydrogens in several polymorphs of palmitic acid. Abstract : The hydrogen-bonding environments at the COOH moiety in eight polycrystalline polymorphs of palmitic acid are explored using solid-state NMR. Although most phases have no previously reported crystal structure, measured 13 C chemical shift tensors for COOH moieties, combined with DFT modeling establish that all phases crystallize with a cyclic dimer ( R 22(8)) hydrogen bonding arrangement. Phases A2, Bm and Em have localized OH hydrogens while phase C has a dynamically disordered OH hydrogen. The phase designated As is a mix of five forms, including 27.4% of Bm and four novel phases not fully characterized here due to insufficient sample mass. For phases A2, Bm, Em, and C the anisotropic uncertainties in the COOH hydrogen atom positions are established using a Monte Carlo sampling scheme. Sampled points are retained or rejected at the ±1 σ level based upon agreement of DFT computed 13 COOH tensors with experimental values. The collection of retained hydrogen positions bear a remarkable resemblance to the anisotropic displacement parameters ( i.e. thermal ellipsoids) from diffraction studies. We posit that this similarity is no mere coincidence and that the two are fundamentally related. The volumes of NMR-derived anisotropic displacement ellipsoids for phases with localized OH hydrogens are 4.1 times smaller than those derived from single crystal X-ray diffraction and 1.8 times smaller than the volume of benchmark single crystal neutron diffraction values.